Managment of Relapsed/Refractory ALL With Inotuzumab During COVID-19. A Casr Report - Martina Di Palma; Elio Gentilini; Chiara Masucci; Alessandra Micozzi; Ombretta Turriziani; Antonino Mulè; Robin Foà; Maurizio Martelli; Gabriella D'Ettorre; Saveria Capria; Sabina Chiaretti (Mediterranean Journal of Hematology and Infectious Diseases)
Management of patients with concomitant acute lymphoblastic leukemia (ALL) and COVID-19 infection is challenging. We describe the clinical history of a 40-year-old male with relapsed B-common ALL who developed Sars-CoV2 prior to treatment initiation with inotuzumab. Since the patient was asymptomatic for COVID-19, the first dose of inotuzumab was administered, followed by remdesivir as prophylaxis. However, a worsening in respiratory findings led to a delay in administering the following doses of inotuzumab. Interestingly, even if the patient did not receive the full inotuzumab cycle, he achieved a complete hematologic remission: furthermore, he spontaneously developed anti-sars-COV2 antibodies. COVID-19 treatment also included convalescent plasma, leading to negativization of the viral load. The patient, after COVID-19 recovery, received a second full cycle of inotuzumab, underwent allogeneic transplantation, and is currently in complete hematologic and molecular remission, in good clinical conditions, five months from allograft.